Application of asymptotic methods to the investigation of one-frequency nonlinear oscillations of cylindrical shells interacting with moving fluid - Koval’chuk, P. S.; Kruk, L. A.; Kubenko, V. D.; Ковальчук, П. С.; Крук, Л. А.; Кубенко, В. Д.; Ковальчук, П. С.; Крук, Л. А.; Кубенко, В. Д. (Institute of Mathematics, NAS of Ukraine, 2007)
We demonstrate the applicability of the Bogolyubov-Mitropol’skii asymptotic method to the construction of one-frequency solutions of a system of nonlinear equations used to describe the multimode free, forced, and parametrically excited vibrations of cylindrical shells interacting with moving fluid.